Spectrophotometric Determination Profile Of Bisphenol A In The Photodegradation Process With Singlet Molecular Oxygen - Doria Herrera, Gloria Maria; Peñuela-Meza, Gustavo; Valencia, Gloria Cristina; Gomez, Ingry Natalia; Soltan, Jafar (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this study, a strategy using Partial Least Squares (PLS) as a chemometric tool to establish the robustness of the photosensitized degradation process of Bisphenol A in simulated effluents was assessed. In the first stage of the research, the validation of the methodology that allows the quantification of Bisphenol A (BPA) mixed with the photosensitizer Eosin Y (EOS) in aqueous solution was carried out. Through the use of spectrophotometry as monitoring technique, it was possible to establish the optimal number of factors and the wavelength range, and to determine that ​​was possible to ensure the quantification of BPA by means of PLS, by demonstrating complex formation between BPA and EOS. The RMSE results were 0.004237 at 284 nm and 0.009167 at 524 nm, demonstrating good robustness in the analysis. Next, preliminary tests were carried out on the effect of direct light using a mercury lamp as a source of irradiation. In the case of BPA, it was determined that 100% degradation is achieved at 100 minutes.